2017
DOI: 10.26480/acmy.01.2017.01.03
|View full text |Cite
|
Sign up to set email alerts
|

Leachable Volatile Organic Compounds From Polyethylene Plumbing Plastic Pipes: A Case Study of Medina Al Munawarah, Saudi Arabia

Abstract: The widespread of plastic piping applications in water distribution systems and home plumbing network has brought many health concern dues to the water quality deterioration from the occurrence of leachable organic pollutants into tape water. Among these pollutants, volatile organic molecules are believed to migrate easily from the popular polyethylene piping. This study aimed to screen the occurrence of volatile organic compounds leachable from plastic pipes comprising home water network system in residential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…2). A previous study reported that B. cereus could reduce Cr(VI) -1 with initial concentrations of 60 and 70 mg l by up to 96.7% and 72.1%, respectively (Murugavelh et al, 2013;Shaikh et al, 2017).…”
Section: Resultsmentioning
confidence: 96%
“…2). A previous study reported that B. cereus could reduce Cr(VI) -1 with initial concentrations of 60 and 70 mg l by up to 96.7% and 72.1%, respectively (Murugavelh et al, 2013;Shaikh et al, 2017).…”
Section: Resultsmentioning
confidence: 96%
“…The conditions of chromatographic column lift are as follows: from 10°C to 50°C/min to 300°C and 20:1 to separate injection 40 . The mass spectrometric condition is set as follows: the ionization mode is EI, the electron energy is 70 eV, the ion source temperature was 230°C, the quadrupole temperature was 150°C, the scanning starting point was 30–600°C, the He flow rate is 1 ml/min, and the scanning quality range is 35–550 AMU ( m / z ) 41 …”
Section: Methodsmentioning
confidence: 99%
“…Hydroxymethylfurfural is a kind of furan derivative. It has certain carcinogenic effect on rodents and has potential to be sustainable substitutes for petroleum-based building blocks used in the production of plastics and fine chemicals (Chheda et al, 2007;Sachse et al, 2016;Shaikh et al, 2017).…”
Section: H E M I C a L C O M P O N E N T S F U N C T I O N P R O G mentioning
confidence: 99%